Influence of implementation of salutogenic strategies in beverage factory buildings on the meaningfulness of workers - Oluwatayo, Adedapo A.; Apav, Fabian D. (Frontiers in Built Environment, 2025)
Amid growing global concerns over employee mental health in high-demand industrial sectors, this study examines how salutogenic design strategies influence workers’ sense of meaningfulness within beverage factory environments. Anchored in Aaron Antonovsky’s Salutogenic Model, particularly the Sense of Coherence concept, the research explores how selected architectural features such as natural lighting, greenery, quiet rooms, and ergonomic furniture, affect workers’ perception of purpose and emotional engagement at work. Using a quantitative case study design across three beverage factories in Nigeria, data were analysed through descriptive and inferential statistics to evaluate the predictive relationship between design features and perceived meaningfulness. The results show a weak but positive relationship (R = 0.364, R2 = 0.132), with ergonomic furniture and quiet spaces contributing the most to workers’ wellbeing, though overall effects were statistically modest. The study’s novelty lies in extending salutogenic theory into industrial architecture, a field where human-centered design has been largely overlooked. Findings emphasize that while spatial interventions can support wellbeing, meaningfulness in factory settings also depends on organisational culture and social support systems. The research contributes to the emerging discourse on health-promoting industrial environments, offering insights for architects, employers, and policymakers seeking to align workplace design with sustainable wellbeing goals.